Influence of environmental parameters on the distribution of bacterial lipids in soils from the French Alps: Implications for paleo-reconstructions. (March 2021) - Véquaud, Pierre; Derenne, Sylvie; Anquetil, Christelle; Collin, Sylvie; Poulenard, Jérôme; Sabatier, Pierre; Huguet, Arnaud
Highlights: 3-OH FAs and brGDGTs analyzed in soils from an altitudinal transect in the French Alps. Investigation of the environmental factors controlling the distribution of bacterial lipids. Influence of soil traits predominant over MAAT. Statistical identification of the individual bacterial lipids influenced by MAAT/pH required. Development of local calibrations with MAAT and pH based on such identification. Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are a family of bacterial lipids widely used for temperature and pH reconstructions in terrestrial settings. 3-hydroxy fatty acids (3-OH FAs) with 10–18 carbon atoms, produced by Gram-negative bacteria, have been recently proposed as independent and complementary proxies of temperature and pH in terrestrial environments. Nevertheless, the correlations between mean annual air temperature (MAAT)/pH and bacterial lipid (brGDGTs/3-OH FAs) distributions show a large degree of scatter, as the relative abundance of these lipids is influenced by factors other than temperature and pH. A full understanding of the environmental parameters influencing bacterial lipid distribution in soils is required to increase the reliability of the temperature and pH proxies based on these compounds in terrestrial environments. The aim of this work was to determine and quantify the cumulative effect of environmental parameters on the distribution of both brGDGTs and 3-OH FAs along a well-documented composite altitudinal transect in the French Alps (234–2748 m). Redundancy analysis revealed that the influence of local parameters (pH and to a lesser extent, soil moisture and grain size, related to vegetation and soil types) on brGDGT and 3-OH FA distributions amounted to 48.1% and 26.1%, respectively, and was predominant over MAAT. This likely explained the weak or lack of relationships between MAAT and brGDGT-/3-OH FA-based indices in this region. The identification of lipids whose fractional abundance is correlated with MAAT or pH allowed the development of local calibrations with MAAT/pH applicable in the French Alps, which are representative of highly contrasted microenvironments, reflecting different types of soil and vegetation. The present study highlighted the importance of constraining the environmental factors affecting the distribution of 3-OH FAs and brGDGTs in terrestrial settings prior to any paleoenvironmental reconstruction. Such an approach should be reproduced in other sites, where local factors could also strongly influence the bacterial lipid distribution.